Bridging the Skills in the Age of AI Gap: Strategies for Upskilling and Reskilling in Higher Education - Dr. Azhar Khan; Dr. Sonia Sethi; Dr. Syed Noman Mustafa; Maryam Bibi, (Dialogue Social Science Review (DSSR), 2025)
This article reviews the dire need for upskilling and reskilling in higher education in Pakistan, with examples from the USA, Europe, and Asia. As technology and the labor market continue to reconfigure every aspect of the workforce, the Pakistani education system is more under pressure to prepare graduates for uncharted territory. In the US, community colleges have gradually emerged as powerful national players that offer training at a local level for industries targeting local needs, with backing from the federal Government in laws such as the Workforce Innovation and Opportunity Act. In the European context, lifelong learning is discussed in frameworks such as the European Skills Agenda, where the focus is on vocational education and training pertaining to current market demands. Other countries in Asia, such as Singapore and South Korea, have seen the implementation of inventive policies to ensure that skill development is ongoing; Singapore's Skills Future initiative is one such policy. In spite of these developments, fundamental issues continue to face Pakistan, including misalignment of curricula with national markets, access to training opportunities, and inadequate emphasis on digital literacy. The paper affirms the importance of interaction between education and industry to honor the relevance of any training program. Future actions should involve integrating lifelong learning approaches, revamping curricula to address industry needs, improving digital literacy, and doing intensive work with industries. Further, an immediate focus is required for development in soft skills, aligning emerging technologies for training, and implementing micro-credentials for specific skills in demand. Linking back to the challenges discussed, a confluence of all these in upskilling and reskilling in higher education in Pakistan becomes imperative. Fostering adaptability, inclusivity, and continuous improvement in the way stakeholders can prepare individuals to thrive in a world that grows in complexity and dynamism. The concepts presented aim to contribute to the forthcoming endeavors toward the establishment of a skilled and resilient workforce prepared to counter tomorrow's challenges.